(untitled) (SCIÉNDO INGENIUM, 2022)
In this research we will address the academic training and labor contributions of the Anthropologist and his contribution to the regional development of Freedom, investigating his development and commitment to the region, the problem of research revolves around: How do the academic training and labor contributions of the Anthropologist contribute to the regional development of freedom? The methods used are those of induction and deduction. Analysis and synthesis are part of the research process, basically in the selection of information, its interpretation and contextualization at work. The comparative historical method is an introduction to the ethnography of work. Observation, interview were used throughout the research process. Traditional planning and its new alternatives have not guaranteed a real identification of the problems and motivations for their own social change, professional progress.